Wpływ wdrażania systemów jakości na wzrost konkurencyjności sektora rolno-spożywczego w regionie zachodniopomorskim - Wiktorowski, Krzysztof (Influence of Implementing Quality Systems on the Growth of Competition of Agrarian-Food Sector in West Pomeranian Region, 2006)
In the article the author presents features of West Pomeranian region regarding its placement on the economical map of Poland and aspect of the importance of agrarian-food sector in economic structure of the region. In the next part of the article he presents the role and importance of implementing quality systems (HACCP, ISO 9001:2000) and positive use (GMP, GHP) on the growth of competition of the agrarian-food sector in West Pomeranian region. The practical aspect of the article is shown on examples of quality systems, certificates of Grain-Milling Enterprise "PZZ" in Stoislaw (Przedsiębiorstwo Zbożowo-Młynarskie "PZZ" w Stoislawiu) and Communal Quality Mark of Meat Plant AGRYF SA (Społeczny Znak Jakości Zakładów Mięsnych AGRYF SA) in Szczecin.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 488-494